Comparison of Chinese calligraphy and ink painting brushes with Western water-media painting brushes - Ng, Woon Lam (2020)
In the history of Chinese ink painting and Western water-media painting, there is a list of brushes developed over the years. The tools developed are highly related to the skill requirements, techniques developed, and the chosen painting surfaces. In this project, a comparison of Chinese and Western brushworks is made. Through the comparison of Chinese calligraphy and ink painting brushworks and Western water-media painting brushworks and their tools, the advantages of both brushwork application processes can be combined with minor sacrifice of their original capacity. After knowing the strength and weakness of these two categories of brushwork application, the results can be introduced to current commercial applications including animation, digital painting, and digital image processing.